Career Orientation of Accounting Student of Brawijaya University - Yasmine Adinda Umar (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2020)
This study purpose is to analyse the factors that influence the career orientation of accounting students at Brawijaya University. The variables used in this study were career orientation of accounting student, ethics (idealism & relativism), gender, age, and knowledge level. The population in this study were accounting students from Brawijaya University batch of 2016, 2017, and 2018. The research study sample is 270 students from a total population of 830 students. Data were collected using random sampling technique. The analysis was carried out by logistic regression method with SPSS. The test results show that simultaneously the variables affect the career, which are partially oriented, the variables of ethics, gender, and level of knowledge have a significant effect.Keywords: Career orientation, Ethics, Gender, Age, Knowledge Level.